(untitled) (Journal of Agriculture and Environment, 2015)
The experiment was conducted in tomato crop grown under plastic house in farmers’ field condition in two VDCs of Bhaktapur District in two seasons in 2011/2012. The objective of the studies was to train the IPM facilitators for the production and multiplication of bio-control agents (Trichoderma harzianum, Trichoderma viride and Pseudomons fluorescens), to advocate the benefit of bio-control method for protection of crops and reduce the use of chemical pesticides in vegetables and to taste the efficacy of commercially available bio-pesticides. Trichoderma viride, T. harzianum, Pseudomons fluorescens and Bavistin were applied in seed and seedlings treatment, and foliar spray. The result revealed that seed and seedlings treated with T. species and Pseudomons fluorescens were healthier than those treated with chemical fungicides and produced higher yield.